Cultural Clashes: Challenges in Cross Cultural Management - Wang, Wei Jiang (2010)
This research reviews the fields of cultural study and cross cultural management and discusses the impact of cultural diversity on international organizational behaviour. Specifically, the effect of cultural clashes on multi-cultural management is examined. With the development of global economy, more and more companies have noticed the benefits that globalization can bring. Along with the fast expansion of international business, variously cultural environments also lead to challenges to management. However, there are arguments that whether managerial tactics should be adapted to local conditions or not. The viewpoint of “culture-specific” is supported in this research. Thus, in the era of global economy, cultural diversity has to be recognized, understood, and appropriately treated in organizational management. The meaning of culture as well as its impact on management is discussed. Cultural clash is thought to be the main problem that results in miscommunication, misunderstanding, and even chaos in cross cultural management. Multiple case study approach is chosen for this research. Secondary data from various sources is collected to aid the research. The selected cases are presented and discussed one by one. Followed is the summary of these cases. It is argued that mutual understanding and respects is the first step to attain harmony for the management. Language is found to be the most apparent and frequent obstacle. The ability to master a new language is thus emphasized. The creation of third culture is also found to be useful. It is clearly shown that cross cultural training has not attracted enough attention that it deserves. More importantly, to recognize the cultural differences does not mean to be cultural chameleon, which means just accepting the new culture and change everything accordingly. Thus, although the recommendations of this research seem to be common sense, it does encourage managers and companies to confront their deep values and to question them. At last, it is vital to bear in mind that cultural differences also bring immense energy. The tactics to make use of the benefits should be discussed in future research.